Gymnastic-Based Movement Therapy for Children With Neurodevelopmental Disabilities: Results From a Pilot Feasibility Study - Gitimoghaddam, Mojgan; McKellin, William H.; Miller, Anton R.; Weiss, Jonathan A.; Majnemer, Annette; Mâsse, Louise C.; Brant, Rollin; Symington, Vivien; Wishart, Robert L.; Collet, Jean-Paul (Frontiers in Pediatrics, 2019)
Background: Developmental and behavioural issues often limit the participation of children with  neurodevelopmental disabilities (NDD) in community-based activities with their peers, which  decreases opportunities for their social learning and development. Parents of children with NDD seek  out programs that address physical and psychosocial development, and more research is needed on the   outcomes associated with this participation. In the planning stage of a large prospective study to assess  the effectiveness of physical activity programs we reviewed the records of children who participated in  a gymnastic-based, one to one, child-centred program, the Empowering Steps Movement Therapy   (ESMT) to explore the potential benefits for children with NDD and their families. Design: This is a historical cohort: the files of 67children with NDD were examined across a 2-year  period (Jan 2011 to Jan 2013). As part of standard practice, the ESMT therapists document changes in  motor function every 6 months, using the ESMT’s proprietary motor scale. Parents also completed a parental questionnaire in June 2011 regarding their perceptions of changes in their child’s physical and  psychosocial function, as well as family functioning since their child started the ESMT program. Results: Linear Mixed Effects Model showed an average monthly change in motor function score  during the two-year study of 1.30 (95% CI: 0.95-1.6); p<0.0001, independent of age at first assessment,  type of diagnosis, baseline score and duration of previous exposure to the program. Parental questionnaires (n=39) reported improvement in most of the children’s physical and psychosocial abilities; they also indicated improvement in most of the family parameters. There was no association  between the changes in children’s motor functions and parents' responses to the questionnaire. Conclusion: Despite the limitations due to the retrospective nature of the study, the absence of a control  group and the absence of validated measurement tools, the association between children's ESMT  program attendance and motor performance and psychosocial development warrants further, rigorous  investigation using validated instruments, independent assessors and control groups.